Prognostic Value and Potential Mechanism of MTFR2 in Lung Adenocarcinoma - Lian, Zengzhi; Pang, Pei; Zhu, Yan; Du, Wenwen; Zhou, Jintao (Frontiers in Oncology, 2022)
Mitochondrial fission regulator 2 (MTFR2) belongs to the MTFR1 family, which plays a crucial role in regulating oxidative phosphorylation. Recent studies indicate that it also participates in cancer carcinogenesis and development, however, the clinical significance of MTFR2 in lung adenocarcinoma has not been fully confirmed. Our current study investigated the relationships between clinical characteristics and MTFR2 expression based on the cancer genome atlas (TCGA), gene expression omnibus (GSE31210) dataset and clinical histopathological samples cohort. In addition, Kaplan-Meier and Cox regression analyses were additionally performed to evaluate the association between MTFR2 expression and patient survival. Gene set enrichment analysis (GESA) was conducted to spot possible pathways associated with MTFR2. Moreover, a single sample GESA (ssGESA) was performed to evaluate the association between MTFR2 expression and immune cells infiltration. Cell colony formation assay, CCK-8 assay, cell cycle assay and transwell assay were performed to verify the cell proliferation, migration and invasion abilities after interfering with MTFR2 in lung cancer cells. Western blot assay was applied to identify the underlying proteins levels. The results indicated that elevated MTFR2 expression in lung adenocarcinoma samples correlated with T stage (P < 0.001), N stage (P= 0.005), M stage (P = 0.015), Pathological stage (P= 0.002), TP53 status (P < 0.001). Patients with higher MTFR2 expression correlated with poorer overall survival (P <0.01) and progression-free survival (P =0.002). Knockdown of MTFR2 inhibited cell proliferation, migration, and invasion via AKT-cyclin D1 signaling and EMT pathways. Moreover, MTFR2 expression significantly positively correlated with Th2 cells (P<0.001). Taken together, MTFR2 could serve as a novel prognostic indicator and therapeutic target for lung adenocarcinoma.